2004
DOI: 10.3310/hta8480
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture of chronic headache disorders in primary care: randomised controlled trial and economic analysis

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(41 citation statements)
references
References 60 publications
1
39
0
1
Order By: Relevance
“…One study followed the patients for 9 months after the cessation of treatment and found that the clinical benefits of acupuncture still exist. 16 Contrary to these findings, a small study in 39 patients with migraine headache reported that 6 months after the intervention, 54% of patients had relapsed to their preacupuncture state. 17 Clearly, further studies are required to evaluate the long-term effects of acupuncture, of any method, on the frequency and severity of migraine headache.…”
Section: Discussionmentioning
confidence: 91%
“…One study followed the patients for 9 months after the cessation of treatment and found that the clinical benefits of acupuncture still exist. 16 Contrary to these findings, a small study in 39 patients with migraine headache reported that 6 months after the intervention, 54% of patients had relapsed to their preacupuncture state. 17 Clearly, further studies are required to evaluate the long-term effects of acupuncture, of any method, on the frequency and severity of migraine headache.…”
Section: Discussionmentioning
confidence: 91%
“…Because biomedical therapies often provide only small improvements for chronic pain syndromes, these conditions may benefit from the addition of safe and effective treatments and are therefore particularly promising targets for AP analgesia. Although AP seems to be effective for several types of chronic pain, including neck pain [52], back pain [53], migraine [54], and FM pain [55,56], these findings are controversial and were not confirmed by several recent studies [49,57,58,59•].…”
Section: Ap Effects On Clinical Painmentioning
confidence: 96%
“…To date, a number of studies have shown that yoga, massage, and acupuncture have shown an ability to mitigate pain or nonpain symptoms. [10][11][12][13][14][15] However, the effect sizes of these benefits have been modest, and none appear to eradicate pain completely.…”
Section: Introductionmentioning
confidence: 93%